2010
DOI: 10.1097/aog.0b013e3181fb540f
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Examinations and Access to Oral Hormonal Contraception

Abstract: OBJECTIVE Requiring a pelvic examination before prescribing oral contraception poses an unnecessary barrier to contraceptive access. Medical guidelines have outlined the safety of oral contraception provision without a pelvic examination, yet little is known about the practices of clinicians providing reproductive health care. Our purpose was to investigate clinicians′ requirements for pelvic examination and what may account for practice differences. METHODS We administered a mailed survey to a national prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 25 publications
0
25
1
Order By: Relevance
“…Usual source of healthcare and current birth control use as significant variables impacting cervical cancer screening frequency has also been supported by previous research (36, 43, 44). Pap tests and pelvic exams often are used as a prerequisite for birth control prescriptions, despite guidelines indicating they are unnecessary (45, 46). The relationship between birth control use and Pap test receipt among young adults is significant, considering 36.6% of all women ages 18–29 years in the 2010 NHIS (data not shown) and 41.3% of this study sample report current birth control use.…”
Section: Discussionmentioning
confidence: 99%
“…Usual source of healthcare and current birth control use as significant variables impacting cervical cancer screening frequency has also been supported by previous research (36, 43, 44). Pap tests and pelvic exams often are used as a prerequisite for birth control prescriptions, despite guidelines indicating they are unnecessary (45, 46). The relationship between birth control use and Pap test receipt among young adults is significant, considering 36.6% of all women ages 18–29 years in the 2010 NHIS (data not shown) and 41.3% of this study sample report current birth control use.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 It is also no longer recommended as a requirement before receiving oral contraceptives. 1,8,9 Although many women have had an annual pelvic examination in association with screening for cervical cancer, the interval for this screening has increased to 3-5 years for averagerisk women, calling into question the need to perform an annual bimanual pelvic examination that is not accompanied by a Pap test. 7 In fact, the knowledge that an annual health maintenance visit is likely to include a bimanual pelvic examination, which many women view as invasive and uncomfortable, can cause anxiety 10 and may actually discourage attendance.…”
Section: Introductionmentioning
confidence: 99%
“…GPs seemed to require it less often because most GPs in Italy do not perform bimanual pelvic examination. In contrast, for example in California one-third of clinicians reported that they always require a pelvic examination when prescribing OCs 5. In that report, a similar proportion of gynaecologists and family physicians reported that they always required a pelvic examination when prescribing OCs, but advanced practice nurses specialising in reproductive health were less likely to require the examination 5…”
mentioning
confidence: 94%